Telling tales: Using narratives and story-telling to understand the challenges faced by a sample of self-initiated expatriates in South Africa. Issue 1 (15th April 2019) - Harry, Tinashe Timothy; Dodd, Nicole; Chinyamurindi, Willie
Abstract : Purpose: South Africa has witnessed an increase in self-initiated academic expatriates (SIAEs) coming into the country from all over the world. This movement of labour can result in South Africa performing better than any other African country. However, expatriation is accompanied by several challenges which affect both work and non-work scopes. Given that more is needed to understand the lived experiences of the expatriates, especially self-initiated expatriates from and in Africa, the purpose of this paper is to provide the basis for interventions to assist the expatriates in overcoming challenges by understanding their lived experiences. Design/methodology/approach: The study used an interpretivist approach to understand the lived experiences of SIAEs. The data were collected through the use of unstructured interviews of 25 expatriate academics within South Africa. The individual narratives were analysed through structural and thematic analysis to develop themes. Findings: Through the stories and narratives, the expatriation experience was one framed to be a challenging process. The lived experiences can be grouped into life and career experiences. The life experiences consist of immigration difficulties, family separation, social adjustment difficulties and unavailability of accommodation. Career experiences include remuneration differences, gender discrimination, limited professional development opportunities and communication difficulties, which affect both work and non-work experiences. Person–environment fit did not play a significant role in the experiences of the academic expatriates. Practical implications: The findings showed that the lived experiences of SIAEs in Africa were mostly negative. Higher education institutions looking at hiring academic expatriates should assist the expatriates to have better experiences not only for individual benefit but for institutional benefit as well. However, this role is not only placed in the hands of the organisation but may also require individual effort. Originality/value: The findings outlined in this study provide a picture of the lived experiences of SIAEs in an African context. The findings are fundamental in understanding this neglected sample group in the extant literature. They also assist in advancing literature and proposing possible solutions. All this is important, given global talent shortages which have warranted the need for highly skilled employees in countries like South Africa.